Relationship between national culture and safety climate of multicultural construction workforce in Abu Dhabi - Muhammad, Ahsan (2023)
The high prevalence of accidents in migrant workers and poor safety climate in construction companies of Abu Dhabi is a continuous concern, especially because of multicultural workforce. These workers who originate from different countries brings different national cultures that may have impact on safety climate of the companies. United Arab Emirates is a country with 91% migrant population, and in the absence of any comprehensive study in past in this country, this study has proposed that national culture dimensions of migrant workers have a relationship with safety climate of the companies. The primary objective of this study is to find out relationship between national culture and safety climate, compare national culture dimensions, and the impact of national culture dimensions on safety climate. Furthermore, this study was conducted among Bangladeshi, Indian and Pakistani workers who make up almost 50% of the total migrant workforce in construction industry of Abu Dhabi. A stratified purposive sampling method was used in this cross-sectional study to survey construction workers in six selected construction companies in Mussafah Industrial area and Al Ain industrial area. A total of 128 respondents participated in answering an adapted questionnaire in the language of their choice. This originally English language questionnaire having two parts, Value survey model (VSM) and Nordic safety climate questionnaire (NOSACQ), that was translated into Bengali, Hindi and Urdu, was used to collect national culture dimension information and safety climate perception respectively. For statistical analysis, Statistical Package for the Social Sciences (SPSS) was used. All of the workers were male, with more than half Indian (54.7%), secondly Pakistani (28.1%) and remaining (17.2%) Bangladeshi. 51.6% of them were unskilled or semi-skilled. Overall safety climate for all nationalities was found (Mean=2.36, SD=0.40) with comparison of safety climate perception among different nationals, F-value (0.858), (p = 0.427) at a given level of alpha. Hence, among different nationalities, safety climate was found to be same. The comparison of national culture dimensions between different nationalities was found on individualism F (2,125) = 5.929, p=.003, masculinity F (2,125) = 5.113, p=.007, Long term orientation F (2,125) = 3.116, p=.048, and indulgence vs restraint F (2,125) = 3.526, p=.032 dimensions. Furthermore, the relationship between safety climate and power distance was 0.381 (p = 0.01), between safety climate and long-term orientation was 0.344 (p = 0.01), between safety climate and individualism was 0.196 (p < 0.05), between safety climate and indulgence vs restraint was 0.068 (p = 0.01), between safety climate and uncertainty avoidance was -0.099 (p = 0.01), and between safety climate and masculinity was 0.163 (p = 0.066). Abu Dhabi's construction workers have a poor safety climate. Bangladeshi, Pakistani, and Indian workers differ significantly in their cultural dimensions of individualism, masculinity, long-term orientation, and indulgence vs restraint. Among these cultural dimensions, power distance, individualism, and long-term orientation were positively related to safety climate, while indulgence, masculinity, and uncertainty avoidance had no significant relationship with safety climate. Power distance and long-term orientation were the most significant contributors to the variation in safety climate.